PEMBUATAN DISPLAY PEMANGGIL PERAWAT OTOMATIS - Almahmudy, Muhammad Iqbal; Gea Mutia Muntari Insani; Febriansyah, Aan; Khasanah, Nur (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
With current advances in technology, an automatic nurse call display system was designed that patients can easily ask for help from a nurse via a calling device that is connected wirelessly to the display unit in the nurse's room. This research aims to design and implement an automatic nurse call display system which is expected to increase the efficiency and responsiveness of nursing services in hospitals. When the patient presses the button in the Blynk application, the display will receive a signal which will display the patient's room number, patient name, and what complaint the patient needs. The method used in making this automatic nurse call display is controlled by an Arduino Uno microcontroller and uses ESP32 as a tool to transmit data between the patient call device and the display unit in the nurse's room. The results of this study indicate that the system works well by reducing nursing staff response time and increasing patient satisfaction. In other words, the conclusion is that this system works by sending signals from the patient calling device to the display unit in the nurse's station to display requests for help in real-time.